Current and desired organizational culture of the financial system of the province of Huancayo, Peru - Santillán-Zapata, N.A. (2020)
The objective of this investigation was to identify the current organizational culture of the financial system of the province of Huancayo and the culture that they wanted, to serve as a complement to the traditional indicators of the sector. The Organizational Culture Assessment Instrument (OCAI) was practiced on 412 workers from 16 financial institutions. It is a quantitative, non-experimental and descriptive study.